LEGAL NATURE OF INTERNATIONAL MIXED ARBITRATION - Kozyreva, Valentyna P.; Kostiuchenko, Dmytro S. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: general theoretical issues of determining the legal nature of international mixed arbitration are considered; the peculiarities of the activity of each individual type of arbitration are outlined. Methods: the research was conducted using such methods as analysis, synthesis, comparative legal knowledge of the legal nature of mixed arbitration, generalization and modeling of new theoretical knowledge. Results: it is concluded that international mixed arbitration is arbitration intended to settle disputes between states and individuals or legal entities due to differences that arise in the course of their investment activities. Through consideration of each type of arbitration, the features and legal nature of a particular type are determined, which makes it possible to determine the general nature. It is determined that the use of institutional arbitration will be appropriate for the full and objective consideration of a dispute related to foreign investment, as the latter has clear regulations and authority to enforce decisions. Discussion: problems of determining the legal nature of international mixed arbitration.